Valuing the Innovation Potentials of Firms: What Theory Suggests, Practitioners do, and both Implies for Existing Theory - Buchmann, Jan Alexander (Springer, 2015)
Jan Buchmann focuses on the valuation of a firm’s innovation potential based on that firm’s position in its lifecycle. Compared to existing research, the author does not center his research exclusively on mathematical valuation methodologies. Instead, the author compares collected valuation input data, data interpretation approaches, and valuation methodologies suggested by theory with the ones applied by experienced valuation experts in a very structured way by applying a firm typology. Subsequently, he uncovers essential differences between theory and practice and derives theory-extending hypotheses from the uncovered differences.